Comparative Brucella Abortus Antibody Prevalence In Cattle Under Contrasting Husbandry Practices In Uganda - Nizeyimana, Gerald; Mwiine, Frank N.; Ayebazibwe, Chrisostom (Journal of the South African Veterinary Association, 2013)
A study was conducted in the Luwero and Nakasongola districts in central Uganda to determine and compare the prevalence and distribution of antibodies against Brucella abortus in cattle under contrasting husbandry practices, using two serological tests. Three hundred and fifteen serum samples were systematically sampled from 29 farms and subsequently tested using the Rose Bengal plate test (RBPT) and Indirect Antibody Enzyme Linked Immunosorbent Assay (I-ELISA). The overall prevalence of antibodies against Brucella abortus in the Nakasongola and Luwero districts was 2.4% and 4.7% on RBPT, compared with 1.2% and 3.34 % on I-ELISA. There was no significant difference between the results obtained by RBPT and indirect antibody ELISA ( 0.05). It was noted that antibodies against Brucella abortus were widely spread over different farms regardless of the cattle grazing system ( 0.05). Based on the findings, it is feasible to use RBPT as a cheaper screening alternative for brucellosis. A comprehensive national brucellosis study should be undertaken to study the epidemiology and prevalence of brucellosis in Uganda.